2016
DOI: 10.1017/s0950268816001539
|View full text |Cite
|
Sign up to set email alerts
|

A role for flies (Diptera) in the transmission ofCampylobacterto broilers?

Abstract: SUMMARYCampylobacter is the leading cause of bacterial diarrhoeal disease worldwide, with raw and undercooked poultry meat and products the primary source of infection. Colonization of broiler chicken flocks with Campylobacter has proved difficult to prevent, even with high levels of biosecurity. Dipteran flies are proven carriers of Campylobacter and their ingress into broiler houses may contribute to its transmission to broiler chickens. However, this has not been investigated in the UK. Campylobacter was cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…A recent study that investigated biosecurity practices on Australian commercial layer farms showed that wild birds were commonly reported to be present in free-range farms (73%) and it was noted that they are potential sources of diseases that can be transmitted to laying hens (31). Flies have previously been implicated in the transmission of other Campylobacter species to chickens (32). Some water, soil, mite, and dust samples were also PCRpositive for C. hepaticus DNA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that investigated biosecurity practices on Australian commercial layer farms showed that wild birds were commonly reported to be present in free-range farms (73%) and it was noted that they are potential sources of diseases that can be transmitted to laying hens (31). Flies have previously been implicated in the transmission of other Campylobacter species to chickens (32). Some water, soil, mite, and dust samples were also PCRpositive for C. hepaticus DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, installation of fly screens around ventilation openings delayed and reduced Campylobacter colonization in flocks (Hald et al., ). A UK study using multilocus sequence typing demonstrated that flies were carrying broiler‐associated sequence types, responsible for human enteric illness (Royden et al., ). Larger fly populations during summer may be a substantial cause of seasonality and time trends for Campylobacter survival and transmission.…”
Section: Prevention Of Colonization and Contaminationmentioning
confidence: 99%
“…Even with improving farm biosecurity levels the Campylobacter colonisation of broilers is extremely difficult to prevent. 20,21 After approximately two weeks poultry flocks are frequently colonised with C. jejuni without any apparent symptoms.…”
Section: Farm Epidemiologymentioning
confidence: 99%
“…30 Relatively low Campylobacter isolation rates have been recorded from Dipteran flies. 21 However, in the summer the potential of broiler Campylobacter colonisation from this potential reservoir could in theory rise when fly populations increase. 21 Certain investigations have shown no significant overlaps in the Campylobacter populations in poultry and wildlife.…”
mentioning
confidence: 99%
See 1 more Smart Citation